THE EFFECT OF HYPNOTEACHING INTEGRATED EXTENSIVE READING TO IMPROVE STUDENTS’ WRITING SKILLS (A QUASI EXPERIMENTAL AT THE TENTH GRADE STUDENT’S OF SMA N 6 BENGKULU TENGAH) - Hana Rahma Sajidah; Risnawati; Andriadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The low writing ability of students is influenced by various factors including the lack of use of learning media and learning models. The purpose of this study was to determine whether or not there is a significant achievement of using hypnoteaching integrated with extensive reading on students' writing skills at SMA N 6 Bengkulu Tengah. The type of research used is quasi-experiment. The population of this study were tenth grade students at SMA N 6 Bengkulu Tengah. This study used purposive sampling technique in determining two classes as samples, class X1 consisting of 30 students as the control class and class X2 consisting of 30 students as the experimental class consisting of 30 students as the experimental class. Writing test data were taken from control and experimental class students collected by two tests, namely pre-test and post-test. First, the researcher gave a pre-test to both classes. After that, the researcher gave a post-test to both classes. Pre-test and pot-test scores are collected from the essay test. The findings of this research indicate that teaching students' writing skills using a hypnoteaching strategy integrated with extensive reading is very effective. The average pre-test score for the experimental class was 34,00 and the post-test was 68,83. This is proven by the calculated t value (0,231) and t table (2,069) which is greater than the table at the 5% significance level. Next, the hypothesis test obtained a 2-tailed sig (p) of 0.00 while alpha (a) was 0.05 (0.00<0.05). This means that Ho is rejected and H is accepted. So, the use of an hypnoteaching integrated extensive reading to improve students' writing skills has a significant effect.